Islamic Guidance Framework and University Access: A Case Study of Academic Tarbiyah Mentoring at MAN Ciwaringin - Agih, Moh. Firdaos; DZ, Abdus Salam; Aspandi, Ade; Muttaqin, Muhammad Azhar (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study analyzes how an Islamic-based academic guidance framework supports students’ access to state universities at MAN Ciwaringin. Persistent disparities between madrasah and general high school graduates indicate the need for guidance models that integrate academic preparation with the pedagogical principles of Islamic education. Using a qualitative case study design, data were gathered through interviews with students, counselors, and alumni, complemented by observations and program documentation. The analysis focuses on the interaction between structured academic coaching and value-oriented mentoring practices embedded in the school’s tarbiyah tradition. The findings show that the guidance model contributes to three main outcomes: improved understanding of university admission mechanisms, enhanced study strategies aligned with exam requirements, and stronger learning discipline shaped by ethical teacher–student relationships. Rather than functioning as motivational support, mentoring enables reflective planning and informed decision-making regarding university and major selection. The study demonstrates that access to higher education in Islamic schools is influenced not only by academic readiness but also by the coherence between guidance practices, institutional culture, and student support networks. Conceptually, this research contributes to Islamic education by showing how tarbiyah-informed mentoring can operate as a practical mechanism for narrowing access gaps in madrasah contexts.